Minimal Surface‐Based Materials for Topological Elastic Wave Guiding. (12th May 2022) - Guo, Yuning; Rosa, Matheus Inguaggiato Nora; Gupta, Mohit; Dolan, Benjamin Emerson; Fields, Brandon; Valdevit, Lorenzo; Ruzzene, Massimo
Abstract: Materials based on minimal surface geometries have shown superior strength and stiffness at low densities, which makes them promising continuous‐based material platforms for a variety of engineering applications. In this work, it is demonstrated how these mechanical properties can be complemented by dynamic functionalities resulting from robust topological guiding of elastic waves at interfaces that are incorporated into the considered material platforms. Starting from the definition of Schwarz P minimal surface, geometric parametrizations are introduced that break spatial symmetry by forming 1D dimerized and 2D hexagonal minimal surface‐based materials. Breaking of spatial symmetries produces topologically non‐trivial interfaces that support the localization of vibrational modes and the robust propagation of elastic waves along pre‐defined paths. These dynamic properties are predicted through numerical simulations and are illustrated by performing vibration and wave propagation experiments on additively manufactured samples. The introduction of symmetry‐breaking topological interfaces through parametrizations that modify the geometry of periodic minimal surfaces suggests a new strategy to supplement the load‐bearing properties of this class of materials with novel dynamic functionalities. Abstract : Given broad design flexibility, minimal surface‐based materials arise as promising continuous‐based material platforms for a variety of engineering applications. The incorporation of symmetry‐breaking topological interfaces through geometric parametrizations that modify the geometry of periodic minimal surfaces suggests a new strategy to supplement the load‐bearing properties of this class of materials with novel dynamic functionalities.